2008
DOI: 10.1614/ws-07-097.1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Flow and Multiple Herbicide Resistance in Escaped Canola Populations

Abstract: Gene flow among herbicide-resistant (HR) canola varieties can lead to the development of multiple HR canola plants, creating volunteer canola management challenges for producers. In western Canada, escaped populations of HR canola are ubiquitous outside of cultivated fields, yet the extent of gene flow resulting in herbicide resistance trait stacking in individuals within these populations remains unknown. The objectives of this study were to document the presence of single and multiple herbicide resistance tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 28 publications
1
129
0
Order By: Relevance
“…The feral 10 | P a g e two to three times higher than those observed in Selommes, while in western Canada, the seed yield from individual feral plants was comparable to that of the crop (Knispel et al, 2008).…”
Section: Redistribution Of Feral Seed Between Local Populations Versumentioning
confidence: 81%
See 4 more Smart Citations
“…The feral 10 | P a g e two to three times higher than those observed in Selommes, while in western Canada, the seed yield from individual feral plants was comparable to that of the crop (Knispel et al, 2008).…”
Section: Redistribution Of Feral Seed Between Local Populations Versumentioning
confidence: 81%
“…In a continuation of the study by Charters et al (1999), it was observed that one population contained, over a period of twelve years, a genetic signature of a variety that had been obsolete for at least ten of those years. In contrast, based on a preliminary analyses of soil samples at feral oilseed rape roadside sites in western Canada in the greenhouse, Knispel et al (2008) indicated that feral oilseed rape roadside soil seedbanks are small (less than five viable seeds per square metre) and lack substantive dormancy. In total, however, the observations from Europe indicate that feral populations have been sufficiently consistent in their presence and abundance to act as a genetic bridge between past and current oilseed rape varieties.…”
Section: Recruitment From Seed Emerging From the Soil Seedbank Or Fromentioning
confidence: 99%
See 3 more Smart Citations